Developing natural products as potential anti-biofilm agents - Lan Lu; Wei Hu; Zeru Tian; Dandan Yuan; Guojuan Yi; Yangyang Zhou; Qiang Cheng; Jie Zhu; Mingxing Li (BMC, 2019)
Abstract Biofilm is a natural form of bacterial growth ubiquitously in environmental niches. The biofilm formation results in increased resistance to negative environmental influences including resistance to antibiotics and antimicrobial agents. Quorum sensing (QS) is cell-to-cell communication mechanism, which plays an important role in biofilm development and balances the environment when the bacteria density becomes high. Due to the prominent points of biofilms implicated in infectious disease and the spread of multi-drug resistance, it is urgent to discover new antibacterial agents that can regulate biofilm formation and development. Accumulated evidences demonstrated that natural products from plants had antimicrobial and chemo-preventive properties in modulation of biofilm formation in the last two decades. This review will summarize recent studies on the discovery of natural anti-biofilm agents from plants with clear-cut mechanisms or identified molecular addresses, as well as some herbs with unknown mechanisms or unidentified bioactive ingredients. We also focus on the progression of techniques on the extraction and identification of natural anti-biofilm substances. Besides, anti-biofilm therapeutics undergoing clinical trials are discussed. These newly discovered natural anti-biofilm agents are promising candidates which could provide novel strategies for biofilm-associated infections.